Work and health in Switzerland: Immigrants and natives - Rainer Winkelmann (University of Zurich, Socioeconomic Institute, 2002)
This paper is concerned with a comparison of immigrants and Swiss citizens with respect to level of education, labor market outcomes and healthcare utilization. The evidence is based on data for 1999 from the first wave of the Swiss Household Panel. In order to control for confounding influences, linear and non-linear (negative binomial) regressio nmodels are used. The main result is that differences in economic position between immigrants and Swiss nationals tend to be smaller than those found in other countries. The observed differences (higher employment levels of immigrant women, lower earnings of immigrant men, higher healthcare utilization rates of all immigrants) tend to be no larger than those observed between Swiss citizens living in different parts of the country.
Keywords: I1; J3; J61; 330; earnings differentials; doctor visits; Swiss Household Panel